1997
DOI: 10.1097/00004728-199711000-00008
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Temporomandibular Joint Disk and Posterior Disk Attachment Before and After Nonsurgical Treatment

Abstract: These results suggest an association between a decrease in contrast enhancement of the posterior disk attachment and resolution or reduction in joint pain. This association was much stronger than the association between the clinical findings and the anatomy of the disk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…A number of studies have investigated the causes of TMJ pain, including impingement and compression of the retrodiscal tissue [26, 27], inflammatory change in the retrodiscal tissue [28, 29], inflammatory change in the joint space resulting in joint effusion [30], capsulitis [31, 32], osteoarthritis [3339], and alteration in the condylar bone marrow of the mandible [9, 11, 15]. Sano et al [9] showed an association between a marked increase in pain and alteration in the bone marrow of the mandibular condyle.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the causes of TMJ pain, including impingement and compression of the retrodiscal tissue [26, 27], inflammatory change in the retrodiscal tissue [28, 29], inflammatory change in the joint space resulting in joint effusion [30], capsulitis [31, 32], osteoarthritis [3339], and alteration in the condylar bone marrow of the mandible [9, 11, 15]. Sano et al [9] showed an association between a marked increase in pain and alteration in the bone marrow of the mandibular condyle.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we measured the permeability of the intact synovial membrane in a nonarthritic state. Because gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA) is rapidly enhanced in the joint cavity of the TMJ, 5,15 Gd-DTPA (0.5 kDa) must be able to permeate the syno-vial membrane. We also selected 3 contrast reagents-an oligomer-based contrast reagent (CH3-DTPA-Gd; 2.1 kDa), gadolinium-labeled polylysine (Gd-polylysine; 10 kDa), and gadolinium-labeled albumin (Gd-albumin; 74 kDa)-and tried to measure the molecular weight dependency of the permeability of the synovial membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic contrast-enhanced MRI with closed mouth revealed that TMJs with pain or dysfunction had a higher signal intensity than those without pain or dysfunction 22,23) . On T2W images with mouth open, a slight increase in signal intensity in painful joints was observed in comparison with painfree joints 17) .…”
Section: Discussionmentioning
confidence: 98%